The Gulf States in International Political Economy - Coates Ulrichsen, Kristian. author. aut Link
XI, 274 p.
Keywords: Kristian Coates Ulrichsen documents the startling rise of the Arab Gulf States as regional powers with international reach and provides a definitive account of how they have become embedded in the global system of power, politics, and policy-making.